Adaptor Protein-3-Dependent Vacuolar Trafficking Involves a Subpopulation of COPII and HOPS Tethering Proteins . Issue 3 (30th May 2017) - Feng, Qiang-Nan; Song, Shi-Jian; Yu, Shi-Xia; Wang, Jia-Gang; Li, Sha; Zhang, Yan
Abstract : AP-3-mediated vacuolar trafficking of PAT10 involves a subpopulation of COPII and the vacuolar tethering complex HOPS. Abstract: Plant vacuoles are versatile organelles critical for plant growth and responses to environment. Vacuolar proteins are transported from the endoplasmic reticulum via multiple routes in plants. Two classic routes bear great similarity to other phyla with major regulators known, such as COPII and Rab5 GTPases. By contrast, vacuolar trafficking mediated by adaptor protein-3 (AP-3) or that independent of the Golgi has few recognized cargos and none of the regulators. In search of novel regulators for vacuolar trafficking routes and by using a fluorescence-based forward genetic screen, we demonstrated that the multispan transmembrane protein, Arabidopsis ( Arabidopsis thaliana ) PROTEIN S -ACYL TRANSFERASE10 (PAT10), is an AP-3-mediated vacuolar cargo. We show that the tonoplast targeting of PAT10 is mediated by the AP-3 complex but independent of the Rab5-mediated post-Golgi trafficking route. We also report that AP-3-mediated vacuolar trafficking involves a subpopulation of COPII and requires the vacuolar tethering complex HOPS. In addition, we have identified two novel mutant alleles of AP-3δ, whose point mutations interfered with the formation of the AP-3 complex as well as its membrane targeting. The results presented here shed new light on the vacuolar trafficking route mediated by AP-3 in plant cells.